Youth political culture fundamentals: historical aspects - SIEKUNOVA, Iuliia (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2014)
The author of the article made an attempt to analyze the political culture ofSoviet youth of the late twentieth century and associate the same with the phenomenonof the political culture of modern Ukrainian youth